(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Slum housing is one of the most important urban problems that worsened after 2003, migration from cities to other cities was great due to lack of security and poor living conditions. Therefore, cities suffocated with the slum belts surrounding them, forming a burden on the city’s fabric, putting pressure on all infrastructure and social services and negatively affecting the urban fabric, through random, illegal and chaotic housing. This has led to many problems, housing, service, environmental, social and economic. The most prominent of which is the unusual growth in the size of slums areas and the various negative effects that have happened in cities. The research aims to shed light on the most important factors generating this phenomenon, and this would help provide material and human capabilities which help us to solve the phenomenon of random housing in Iraq. Methodology used is descriptive analytical as well as sample-based survey by distributing a questionnaire to a selected sample including different categories from the decision makers categories to the beneficiaries group in the study area. The main conclusions were and still are within the circle of economic reasons represented by low income and unemployment, while social reasons are the search for a better life in Kufa city, which they lack in their former areas.